Pengaruh Debt To Asset Ratio (DAR) Dan Debt To Equity Ratio (DER) Terhadap Return On Assets (ROA) Pada Bank Panin TBK PERIODE 2013–2023 - Angela Anugrah; Dwi Maharani Putri; Suparjono (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the impact of Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) at Bank Panin Tbk for the period 2013–2023. The research method employed is quantitative with both descriptive and verificative approaches. Data were obtained from the annual financial statements of Bank Panin and analyzed using multiple linear regression. The results indicate that DAR has a significant negative effect on ROA, while DER does not have a significant impact. Simultaneously, DAR and DER significantly influence ROA. These findings imply that effective management of debt structure can enhance the financial performance of Bank Panin.